Exploring the motivations behind crafting identities in virtual reality interactions - YUEYAO HU (2025)
Virtual social interaction platforms like VRChat offer users personalised immersive experiences, making it an important space for investigative virtual identity perception. Avatars, as representations of users on virtual social platforms, showcase their personalities, interests, and styles, enabling users to better express their identity. The primary research question is: What motivates users to design avatars in virtual reality (VR)? Many studies are dedicated to explaining the construction and expression of users' online identities. However, the rapid development of emerging technologies presents challenges in keeping research findings relevant to current societal contexts. These efforts encounter a shared challenge, which is capturing the subtle differences and fluidity of identity. To address this challenge, the aim of the research is to explore the relationship between users' motivations for choosing virtual avatars and their self-presentation. The research objectives include analysing users' inspirations, exploring the factors that drive users' avatar modifications, investigating the strategies employed by users for impression management in VR, and examining how virtual cultural environments impact users' personal impression management. Erving Goffman's impression management theory was used as a theoretical lens to understand how individuals construct and manage their identities in digital environments, providing a valuable theoretical framework for understanding online identity research and virtual social interaction. The research methodology used a mixed-methods approach, with a focus on qualitative research. The methods include the use of surveys and interviews, with data analysis conducted through discourse analysis. The methodological framework is primarily rooted in interpretive phenomenology, supplemented by autoethnography as an additional approach. The planned sample size for the surveys was 70 individuals, but the actual number of valid survey responses collected was 77. Additionally, interviews were conducted with a total of 21 participants. The research findings indicate a significant relationship between users' motivations, past experiences, and social situation. Moreover, users exhibit a strong motivation to create, shape, and modify avatars in immersive environments where identity selection is freely available, thus exploring dynamic virtual identities. As virtual interaction progresses, users tend to develop and redefine their identities within a context of belonging, security, and inclusive social environments. In such circumstances, the research evidence suggests a fusion and mutually influential relationship between users' virtual and real-life identities. Overall, the data and analysis of this study support the view that the virtual platforms provide opportunities for the development of and shaping of personal identities. Additionally, it extends the applicability of Erving Goffman's theory to the VR identity field, offering valuable insights into how individuals engage in social interaction in virtual environments.